Advanced consent for participation in acute care randomised control trials: protocol for a scoping review. Issue 10 (16th October 2020) - Niznick, Naomi; Lun, Ronda; Dewar, Brian; Dowlatshahi, Dar; Shamy, Michel
Abstract : Introduction: Informed consent is essential to clinical research, though obtaining informed consent for participation in research for emergency conditions is challenging. Adapted consent methods include consent from a substitute-decision maker, deferral of consent and waiver of consent. A novel approach is to use advanced consent, where a potential participant provides consent in the present in the event that they become eligible for enrolment into a future study. This scoping review will map and synthesise the literature on the use of advanced consent for participation and enrolment in randomised control trials for emergency conditions. Methods and analysis: Guided by Arksey and O'Malley's scoping review methodology framework, we will search electronic databases (Medline, Embase, Web of Science and the Cochrane Register of Clinical Trials), the grey literature sources and reference lists of relevant studies. Eligible studies will include English language articles that discuss, examine or employ the use of advanced consent for enrolment in randomised control trials, specifically related to emergency conditions or emergency treatment. Diverse types of articles will be eligible for inclusion, including peer-reviewed qualitative and quantitative studies such as randomised control trials, observational studies, surveys, systematic reviews, as well as narrative reviews and ethics papers. Studies will be screened by two independent reviewers to determine eligibility for inclusion. Data on bibliographic information, study characteristics and methodology, and reported results, specifically author disposition, will be extracted and described using qualitative analysis. Ethics and dissemination: Formal ethics review is not required as primary data will not be collected. The findings of this study will be disseminated through a peer-reviewed publication. The findings of this study will help identify knowledge gaps that may guide areas for future research and may aid in the design of future clinical trials using advanced consent.